ESTUDO QUÍMICO BIOMONITORADO DE QUATRO ESPÉCIES DA FAMÍLIA MYRTACEAE - Correa, Tayane Fardim (2021)
The Atlantic Forest is one of the most biodiverse Brazilian biomes and has important domains, such as mangroves and restingas. Within the restingas, one of the most expressive families in terms of number of species is the Myrtaceae family. Some of the spe